Post-surgical Dental Precautions/Prophylaxis in Pediatric Patients: Results of a 2023 Survey of the Membership of the Pediatric Orthopaedic Society of North America - James F. Mooney, III, MD; Ariel Brotherton, MA, LAT, ATC; Garrett Bullock, PT, DPT, DPhil; Robert F. Murphy, MD (Elsevier, 2024)
Introduction: Guidelines regarding postsurgical dental care have been common in adult total joint arthroplasty patients despite limited supporting evidence in the literature. There is anecdotal evidence that similar precautions are implemented frequently in postoperative pediatric orthopaedic patients without any published evidence to guide clinicians. Methods: A survey of the Active Members of the Pediatric Orthopaedic Society of North America (POSNA) was performed to assess the use of postsurgical guidelines regarding dental care (procedures and prophylaxis) in pediatric patients. A 20-question survey regarding this subject was developed with the input of, and approved by, the Evidence-Based Practice Committee of POSNA, and a link to participate was distributed to the Active Membership. Results: One hundred seventy-three POSNA Members opened the link to the survey. One hundred sixty-three respondents self-identified as Active, for a response rate of 19.8%. One hundred fifty-seven (96.3%) reported direct involvement in surgical and postsurgical care of pediatric orthopaedic patients. Sixty-two (39.4%) indicated use of a postoperative protocol regarding dental interventions. Forty percent of those indicating use of guidelines were uncertain of the specifics of the protocol(s) used at their institution. Eighty-five percent of those utilizing protocols felt that the use of guidelines was a valuable topic for investigation. Conclusions: These results demonstrate that many of the active Members of POSNA utilize postsurgical guidelines for dental care, particularly for those patients who have undergone spinal surgery with permanent implants. This is despite the fact that there is limited evidence to support their use in adult total joint patients and no literature regarding use of such guidelines in pediatric orthopaedic patients. Key Concepts: (1) There is limited and contradictory evidence that postsurgical dental guidelines are indicated in adult orthopaedic patients. (2) There is no published evidence supporting postsurgical dental guidelines in pediatric orthopaedic patients. (3) Almost 40% of active Pediatric Orthopaedic Society of North America Members responding to a survey appear to utilize postsurgical dental care guidelines in pediatric patients, particularly after spinal procedures utilizing implants. Level of Evidence: Level V